2010
DOI: 10.1266/ggs.85.219
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genomes and novel gene rearrangements in two dicroglossid frogs, Hoplobatrachus tigerinus and Euphlyctis hexadactylus, from Bangladesh

Abstract: We determined the complete nucleotide sequences of mitochondrial (mt) genomes from two dicroglossid frogs, Hoplobatrachus tigerinus (Indian Bullfrog) and Euphlyctis hexadactylus (Indian Green frog). The genome sizes are 20462 bp in H. tigerinus and 20280 bp in E. hexadactylus. Although both genomes encode the typical 37 mt genes, the following unique features are observed: 1) the ND5 genes are duplicated in H. tigerinus that have completely identical sequences, whereas duplicated ND5 genes in E. hexadactylus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 52 publications
(74 reference statements)
5
47
0
Order By: Relevance
“…In contrast to the former, the mt gene arrangement of the Babina sensu stricto group differs from the neobatrachian-type arrangement and shows the unique position of the ps-trnH-trnS (AGY)-nad5 gene region between the CR and the LTPF trn-cluster. The translations of nad5 from its original position (upstream of the CR) to downstream of the CR were reported in several neobatrachian mt genomes (e.g., dicroglossids, rhacophorids, mantellids, and the ranid Staurois latopalmatus; see , Alam et al, 2010. However, the CR downstream position of trnS (AGY) and trnH or its pseudogene is found only in Babina and a few ranid species (S. latopalmatus and Odorrana spp.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast to the former, the mt gene arrangement of the Babina sensu stricto group differs from the neobatrachian-type arrangement and shows the unique position of the ps-trnH-trnS (AGY)-nad5 gene region between the CR and the LTPF trn-cluster. The translations of nad5 from its original position (upstream of the CR) to downstream of the CR were reported in several neobatrachian mt genomes (e.g., dicroglossids, rhacophorids, mantellids, and the ranid Staurois latopalmatus; see , Alam et al, 2010. However, the CR downstream position of trnS (AGY) and trnH or its pseudogene is found only in Babina and a few ranid species (S. latopalmatus and Odorrana spp.…”
Section: Resultsmentioning
confidence: 96%
“…These sequences could be folded into typical cloverleaf structures and hold the same anticodon, CAT, which is common in most metazoan mt tRNA-Met genes. Although, two tRNA-Met genes have been reported in the complete mtDNA of F. cancrivora (Ren et al 2009), F. limnocharis (Liu et al 2005), L. bannaensis ), L. fujianensis (unpublished data), H. rugulosus (Yu et al 2012), H. tigerinus, E. hexadactylus (Alam et al 2010), P. spinosa (Zhou et al 2009) and M. madagascariensis (Kurabayashi et al 2006), the position of the extra tRNA-Met gene differs between Dicroglossidae and Mantellidae. Based on these differences, Kurabayashi et al (2006) suggested that two tRNA-Met genes in each lineage are of different origin.…”
Section: Two Tandem Trna-met Genes and Gene Rearrangementmentioning
confidence: 99%
“…We prepared two datasets: (1) a dataset containing all haplotypes from five Hoplobatrachus species in South and Southeast Asia and (2) a dataset containing H. tigerinus haplotypes in Bangladesh. In dataset (1), we also included H. chinensis and Euphlyctis hexadactylus CYTB haplotypes previously reported by Alam et al (2010Alam et al ( , 2012) (accession numbers: AB636597-AB636600 and AP011544). Based on this dataset, we constructed a Hoplobatrachus species phylogenetic tree using the neighbor-joining (NJ) (Saitou and Nei, 1987) and maximum likelihood (ML) methods.…”
Section: Inference Of Phylogenetic Relationships and Genetic Diversitymentioning
confidence: 99%